Adsorption of Congo Red dye on CuO nanoparticles synthesized by green method using Nyctanthes arbor‐tristis leaf extract: Experimental and theoretical study. Issue 9 (23rd June 2022) - Jethave, Ganesh; Fegade, Umesh; Inamuddin,; Altalhi, Tariq; Khan, Mohd. Farhan; Barhate, Bhojraj; Suryawanshi, Kiran E.; Isai, Kalpesh A.
Abstract: Copper oxide nanoparticles (CONs) are synthesized using the leaf extract of Nyctanthes arbor‐tristis . They are further characterized using FE‐SEM and EDX techniques and successfully used for the removal of Congo Red (CR) dye. To enhance the removal efficiency, the effect of various parameters viz. shaking time, adsorbent dose, pH, etc. are studied. The kinetic model showed that the CR adsorption on CON followed the pseudo‐first‐order reactions. Langmuir isotherm modeling is best fitted and describes the CR‐CON adsorption system for CR dye in 90 min with Q max at 333.33 (mg/g). At varying temperatures, the statistical physics model computed the number of bound CR dye molecules and the saturation adsorption capacity for both functional groups. At 298, 308, and 318 K, the values of " n " are 0.379, 0.358, and 0.328, respectively, which showed that CR molecules interacted with two and three functional groups of the CON surface through a horizontal adsorption orientation. The role and importance of suggested functional groups on dye adsorption as well as their thermodynamic characteristics are determined using a statistical physics model. The reused study is applied to the CON and their efficiency is excellent up to five cycles, making CON an effective pollution control material that may be commercialized in the near future.